Pesan Dakwah Islam-Modern dalam Tafsir Berbahasa Sunda Nurul-Bajan dan Ayat Suci Lenyepaneun - Lathief, Afief Abdul (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
Daâwah could be done with use all chanel, one of them through writing the quranic exsegese book. Especially the exsegese book is written by Muhammad Romli and Moh. E. Kosim, another the exegese is unique of using Sundanese language, also because the contents ideological nuances. The ideological characteristic appear in writterâs effort that representate the ideology of modern Islam criticize traditional Islam group especially NU community of tussle with deviate and sincretis faiths as named taqlid, jumud, bidâah, khurafat, takhayyul, ngaruat ceremony, nadran, tiluna, tujuhna and so on.